2022
DOI: 10.3390/s22062172
|View full text |Cite
|
Sign up to set email alerts
|

Toward Dependable Internet of Medical Things: IEEE 802.15.6 Ultra-Wideband Physical Layer Utilizing Superorthogonal Convolutional Code

Abstract: Wireless body area networks (WBANs) are attracting attention as a very important technology for realizing an Internet of Medical Things (IoMT). IEEE 802.15.6 is well known as one of the international standards for WBANs for the IoMT. This article proposes the combination of the IEEE 802.15.6 ultra-wideband (UWB) physical layer (PHY) with a super orthogonal convolutional code (SOOC) and evaluates its performance as a dependable WBAN. Numerical results show that sufficient dependability cannot be obtained with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Ref. [38] confirmed the higher dependability obtained by concatenating an SOCC and a Reed-Solomon (RS) code under additive white Gaussian noise (AWGN) and the WBAN channel model referenced in [30].…”
Section: Related Worksupporting
confidence: 53%
See 4 more Smart Citations
“…Ref. [38] confirmed the higher dependability obtained by concatenating an SOCC and a Reed-Solomon (RS) code under additive white Gaussian noise (AWGN) and the WBAN channel model referenced in [30].…”
Section: Related Worksupporting
confidence: 53%
“…Our own previous research presented a quality-of-service (QoS) control scheme utilizing decomposable codes for an IEEE 802.15.6 based UWB-WBAN [37]. In addition, our previous research reported a performance evaluation in terms of the transmission failure ratio and energy efficiency for the UWB PHY of IEEE 802.15.6 under the application of a super-orthogonal convolutional code (SOCC) [38]. Ref.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations